1997
DOI: 10.1515/znc-1997-9-1004
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Flavonoids as Chemotaxonomic Markers for Two Erythroxylum Taxa

Abstract: Leaf extracts of Erythroxylum coca var. coca Lam. (E. c. var. coca) yielded six O-eonjugates of Eriodictyol flavonoids, while the equivalent extracts from Erythroxylum novograna tense var. novogranatense (Morris) Hieron (E. n. var. novogranatense) contained five flavo noids, two of which were O-conjugates of Luteolin and three were O-conjugates of Kaempferol. All six of E. c. var. coca methanolic extracted peaks (resolved by HPLC) were found to have a 2, 3 single bond, which in E. n. var. novogranatense is rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…coca) as one transplanted and grown under field conditions for two years with leaves being harvested six times per year. This observation on cultivating coca is also the consensus of local coca growers interviewed in Bolivia and Peru in 1994, and 1995 (15). Accordingly, the juvenile growth period for E.c.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…coca) as one transplanted and grown under field conditions for two years with leaves being harvested six times per year. This observation on cultivating coca is also the consensus of local coca growers interviewed in Bolivia and Peru in 1994, and 1995 (15). Accordingly, the juvenile growth period for E.c.…”
Section: Introductionsupporting
confidence: 72%
“…The foliage of these plants is used in traditional medicines and as a source for the cocaine alkaloid (12,31,33). Although the floral anatomy, seed embryology, ethnobotany, and phytochemistry for the taxa have been described (2)(3)(4)6,9,11,(13)(14)(15)19,21,23,(25)(26)(27)(28)(29)(30)(31)34,(37)(38)(39), past and present research on the two species has focused on constituents within mature plants, plant parts, and/or tissue derived from the plants (1,3,4,(7)(8)(9)11,12,14,15,19,21,30,32,33,35). Information on alkaloid composition and content in the plant tissue during the latter stage of seed maturation and during juvenile growth is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These findings supported their linear evolutionary progression hypothesis. However, more detailed investigations into the flavonoid chemistry of the cultivated taxa (Johnson et al 1997(Johnson et al , 1998(Johnson et al , 2002(Johnson et al , 2003a found few similarities in flavonoid profiles.…”
Section: Relationships Among Cultivated Erythroxylum Taxamentioning
confidence: 99%
“…Chemically, the genus is characterized by the presence of tropane alkaloids. Also were also isolated flavonoids, terpenes, and tannins (Ansell, et al, 1993;Barreiros, et al, 2002;Brock, et al, 2005;Chávez, et al, 1996;González-Guevara, et al, 2006;Johnson, et al, 1997;Zuanazzi, et al, 2001). Erythroxylum coca Lamk.…”
Section: Introductionmentioning
confidence: 98%